Sistem Pembinaan Anak Binaan di Lembaga Pembinaan Khusus Anak (LPKA) Klas I Tanjung Gusta Medan - Sari Kartika Sembiring; Madiasa Ablisar; Marlina Marlina; Edy Ikhsan (USU LAW JOURNAL, 2019)
Abstract. The System of Practice embraced by Indonesia, regulated in Law No.12 of 1995 on Correctionalism gives meaning to the development of "Penitentiary System" sourced and based on Pancasila and the 1945 Constitution, which provides a strong legal basis in establishing the implementation of "Penitentiary System "Which has been used to nurture and support prisoners since 1964, to replace the prison system. This research uses normative juridical legal research methods supported by empirical. The normative-empirical approach is based on direct experience or observation to see and tack on some sociological issues concerning the principles of law, legal doctrines, rule of law and legal system. Field study is a procedure performed with observation activities, interviews (interview) to the research response as an effort to collect various data and iformasi needed in accordance with the problems discussed in the study. The guidance system carried out in LPKA Class I Tanjung Gusta Medan has been well implemented but the  implementation is not effective due to overcapacity or overpopulation. LPKA's task is to provide guidance to assisted children. This guide is provided with attached description of the process and stages of fostering. Obstacles and efforts in the implementation of the guidance of the guidance children in LPKA Class I Tanjung Gusta Medan is the lack of facilities and infrastructure in the process of coaching, prison students beyond the tamping power, lack of budget (fund), limited number of personnel officers in LPKA environment.   Keywords: guidance, child development, penitentiary